A Simple and High-performance Platform for Refractive Index Sensing based on Plasmonic Metal Disks on a Metal Mirror. (March 2019) - Liu, Xianchao; Ma, Rui; Sutherland, Duncan; Wang, Jun
Abstract: Numerical simulations are used to study light interactions with a platform composed of arrays of stacked metal and spacer dielectric disks on a continuous Au film. Tunable and high absorption is obtained near 1.6 μm by adjusting the thickness of the dielectric disks. Nearly perfect-absorption remains for a wide range of disk diameters. The near-perfect absorption is attributed to a magnetic resonance within the dielectric disks (combined with electric resonance at the metal disks) inducing the platform response to incident light. In addition, the resonance response to environment is more sensitive than that of metal disks on dielectric/metal films. Furthermore, when the diameter of the dielectric disks is reduced, the local electromagnetic field is more exposed and the refractive index sensitivity (RIS) increases to 1133nm/RIU (refractive index unit). The method is simple and effective to improve RIS of sandwich plasmonic structures and will be adopted in various plasmonic devices.